Lithium battery solid electrolyte coating based on sodium amino sulfonated cellulose, preparation method and negative pole piece of lithium battery solid electrolyte coating
By modifying carbon fiber and etching copper foil, the problem of insufficient contact between carbon fiber and solid electrolyte was solved, improving conductivity and peel strength, and enhancing battery performance.
Patent Information
- Application Number
- CN202610197623.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-11
- Publication Date
- 2026-03-20
AI Technical Summary
The existing carbon fiber has insufficient contact ability with the solid electrolyte, resulting in insufficient conductivity and peel strength between the solid electrolyte coating and the negative electrode current collector.
Modified carbon fiber is used as a conductive agent. The surface roughness of the carbon fiber is increased by treating it with concentrated nitric acid and copper nitrate solution. After depositing copper oxide particles on the surface of the carbon fiber, it is reduced to copper particles. Combined with the etching treatment of copper foil, a good conductive network and enhanced contact are formed.
This improved the contact ability between carbon fiber and solid electrolyte, enhanced conductivity and the peel strength between the solid electrolyte coating and copper foil, and improved the conductivity and stability of the battery.
Smart Images

Figure CN121709701A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid electrolyte coating technology, specifically to a lithium battery solid electrolyte coating based on sodium aminosulfonated cellulose, its preparation method, and its negative electrode sheet. Background Technology
[0002] Solid electrolyte coating refers to coating the electrode surface with a layer of solid electrolyte material to provide a continuous ion transport path and reduce the interfacial resistance between the electrode and the electrolyte. This coating can significantly improve the overall performance of the battery, especially in all-solid-state batteries, where the application of solid electrolyte coatings is particularly important.
[0003] Solid electrolyte coatings can effectively reduce the interface resistance of batteries and improve their rate performance and cycle stability.
[0004] Solid electrolyte coatings consist of a solid electrolyte, a conductive agent, and a binder. Common conductive agents often use particulate materials such as graphite, which have point-to-point contact with the solid electrolyte. To improve conductivity, researchers have found that using carbon fibers can achieve better conductivity. Carbon fibers have a linear structure, easily forming a good conductive network in the electrode, exhibiting better conductivity. This reduces electrode polarization, lowers battery internal resistance, and improves battery performance. Inside the battery where carbon fibers are used as the conductive agent, the contact between the active material and the conductive agent is a point-to-line contact. Compared to the point-to-point contact between conductive carbon black and conductive graphite, this not only improves electrode conductivity but also reduces the amount of conductive agent needed, increasing battery capacity.
[0005] However, the surface of carbon fiber is generally smooth, which allows for further improvement in its contact ability with solid electrolytes and thus enhances its performance. Therefore, those skilled in the art have proposed a solid electrolyte coating that not only further improves the contact ability between carbon fiber and solid electrolyte but also ensures high peel strength between the prepared solid electrolyte coating and the negative electrode current collector. Summary of the Invention
[0006] The purpose of this invention is to provide a lithium battery solid electrolyte coating based on sodium aminosulfonated cellulose, its preparation method, and its negative electrode sheet, so as to solve the problems mentioned in the background art.
[0007] To achieve the above objectives, the present invention provides the following technical solution: The preparation method of the solid electrolyte coating for lithium batteries based on sodium aminosulfonated cellulose includes the following steps: S1. Grind the solid electrolyte to a particle size of less than 50nm; S2. Add the solid electrolyte treated in step S1 to deionized water, then add the binder and conductive agent, stir and mix evenly to obtain a slurry; S3. The slurry obtained in step S2 is coated onto the surface of the substrate and dried to obtain a solid electrolyte coating. The conductive agent is modified carbon fiber; The method for preparing the modified carbon fiber includes the following steps: S101. Place the carbon fiber in concentrated nitric acid and heat it for 2-4 hours. Then, wash the carbon fiber treated with concentrated nitric acid with sufficient deionized water and dry it to constant weight at room temperature. S102. The carbon fibers treated in step S101 are heated in copper nitrate solution for 10-20 hours. After that, the carbon fibers are taken out and dried to constant weight at room temperature. The dried carbon fibers are then heated in air at 220-270℃ for 1-4 hours. S103. The carbon fibers treated in step S102 are heated in a hydrogen atmosphere at 400-500℃ for 2-4 hours, and then cooled to room temperature to obtain modified carbon fibers.
[0008] Furthermore, the solid electrolyte in step S1 is either LLZO or LATP; the binder in step S2 is sodium aminosulfonated cellulose.
[0009] Furthermore, in step S2, the mass ratio of the solid electrolyte, conductive agent, deionized water, and adhesive is (5-10):(4-6):(20-25):1.
[0010] Furthermore, in step S101, the concentration of concentrated nitric acid is 68 wt%, the temperature at which the carbon fiber is heated in concentrated nitric acid is 80-100°C, and the mass ratio between concentrated nitric acid and carbon fiber added to concentrated nitric acid is 10:1.
[0011] Furthermore, in step S102, the concentration of the copper nitrate solution is 0.5-2 mol / L, the mass ratio between the copper nitrate solution and the carbon fibers added to the copper nitrate solution is 15:1, and the temperature at which the carbon fibers are heated in the copper nitrate solution is 50-70℃.
[0012] The lithium battery solid electrolyte coating based on sodium aminosulfonated cellulose was prepared by the above-described method for preparing a lithium battery solid electrolyte coating based on sodium aminosulfonated cellulose.
[0013] A negative electrode sheet comprising the above-mentioned lithium battery solid electrolyte coating based on sodium aminosulfonated cellulose; The negative electrode sheet also includes a negative current collector and a negative active material coating.
[0014] Furthermore, the negative electrode current collector is a copper foil, and the solid electrolyte coating is coated on both sides of the negative electrode current collector; the negative electrode active material coating is coated on the surface of the solid electrolyte coating; the negative electrode active material coating is composed of styrene-butadiene rubber (SBR), soft carbon, conductive graphite, and deionized water; the mass ratio of SBR, soft carbon, conductive graphite, and deionized water is 1:25:4:45.
[0015] Furthermore, the copper foil needs to undergo surface treatment, and the method for surface treatment of the copper foil is as follows: After the copper foil surface is polished, it is immersed in a mixed solution of potassium persulfate and sodium hydroxide for etching. The etching time is 30-50 minutes and the etching temperature is 40-60℃. After etching, the copper foil is washed with sufficient deionized water and dried at room temperature.
[0016] Furthermore, the concentrations of potassium persulfate and sodium hydroxide in the mixed solution are 0.01-0.5 mol / L and 0.5-1 mol / L, respectively.
[0017] Compared with the prior art, the beneficial effects of the present invention are: 1. The conductive agent in this invention uses modified carbon fiber. Carbon fiber has a linear structure, forming a good conductive network, which improves conductivity. The contact form between the active substance and the carbon fiber is point-line contact. In this invention, the surface of the carbon fiber is treated with concentrated nitric acid, which greatly increases the surface roughness of the carbon fiber, further enhances the contact ability between the carbon fiber and the solid electrolyte, and improves its conductivity. 2. In this invention, copper oxide is deposited on the surface of rough carbon fiber, and then the copper oxide particles are reduced to copper particles through a reduction reaction. The copper particles also have excellent conductivity and good contact with copper foil. Further etching treatment on the surface of copper foil makes its surface concave and rough. The copper particles, together with the rough carbon fiber, effectively enhance the contact between the solid electrolyte coating and the copper foil, and improve the peel strength. Attached Figure Description
[0018] Figure 1 This is a process flow diagram for preparing the solid electrolyte coating in this invention; Figure 2 This is a process flow diagram for preparing modified carbon fibers in this invention. Detailed Implementation
[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] Please see Figures 1 to 2 The present invention provides: Example 1 The preparation method of the solid electrolyte coating for lithium batteries based on sodium aminosulfonated cellulose includes the following steps: S1. Grind the solid electrolyte, which is LLZO, to a particle size of less than 50nm. S2. Add 10g of solid electrolyte treated in step S1 to 35g of deionized water, then add 1.6g of binder and 8.5g of conductive agent. The binder is sodium aminosulfonated cellulose and the conductive agent is modified carbon fiber. Stir and mix evenly to obtain a slurry. S3. The slurry obtained in step S2 is coated onto the surface of the substrate and dried to obtain a solid electrolyte coating. The preparation method of the above-mentioned modified carbon fiber includes the following steps: S101. Place 15g of carbon fiber into 150g of concentrated nitric acid with a concentration of 68wt%, heat to 90℃ for 3h, and then wash the carbon fiber treated with concentrated nitric acid with sufficient deionized water and dry it to constant weight at room temperature. S102. 10g of carbon fiber treated in step S101 is heated to 60°C for 12h in 150g of copper nitrate solution with a concentration of 1.2mol / L. After that, the carbon fiber is taken out and dried to constant weight at room temperature. The dried carbon fiber is then heated in air at 240°C for 5h. S103. The carbon fibers treated in step S102 are heated in a hydrogen atmosphere at 450°C for 2.5 hours, and then cooled to room temperature to obtain modified carbon fibers.
[0021] Example 2 The preparation method of the solid electrolyte coating for lithium batteries based on sodium aminosulfonated cellulose includes the following steps: S1. Grind the solid electrolyte, which is LATP, to a particle size of less than 50 nm. S2. Add 10g of solid electrolyte treated in step S1 to 40g of deionized water, then add 2g of binder and 8g of conductive agent. The binder is sodium aminosulfonated cellulose and the conductive agent is modified carbon fiber. Stir and mix evenly to obtain slurry. S3. The slurry obtained in step S2 is coated onto the surface of the substrate and dried to obtain a solid electrolyte coating. The preparation method of the above-mentioned modified carbon fiber includes the following steps: S101. Place 15g of carbon fiber into 150g of concentrated nitric acid with a concentration of 68wt%, heat to 80℃ for 2h, and then wash the carbon fiber treated with concentrated nitric acid with sufficient deionized water and dry it to constant weight at room temperature. S102. 10g of carbon fiber treated in step S101 is heated to 50°C in 150g of 0.5mol / L copper nitrate solution for 10h. After that, the carbon fiber is taken out and dried to constant weight at room temperature. The dried carbon fiber is then calcined in air at 220°C for 1h. S103. The carbon fibers treated in step S102 are heated in a hydrogen atmosphere at 400°C for 2 hours, and then cooled to room temperature to obtain modified carbon fibers.
[0022] Example 3 The preparation method of the solid electrolyte coating for lithium batteries based on sodium aminosulfonated cellulose includes the following steps: S1. Grind the solid electrolyte, which is LLZO, to a particle size of less than 50nm. S2. Add 10g of solid electrolyte treated in step S1 to 25g of deionized water, then add 1g of binder and 6g of conductive agent. The binder is sodium aminosulfonated cellulose and the conductive agent is modified carbon fiber. Stir and mix evenly to obtain a slurry. S3. The slurry obtained in step S2 is coated onto the surface of the substrate and dried to obtain a solid electrolyte coating. The preparation method of the above-mentioned modified carbon fiber includes the following steps: S101. Place 15g of carbon fiber into 150g of concentrated nitric acid with a concentration of 68wt%, heat to 100℃ for 2h, and then wash the carbon fiber treated with concentrated nitric acid with sufficient deionized water and dry it to constant weight at room temperature. S102. 10g of carbon fiber treated in step S101 is heated to 70°C in 150g of copper nitrate solution with a concentration of 2mol / L for 20h. After that, the carbon fiber is taken out and dried to constant weight at room temperature. The dried carbon fiber is then heated in air at 270°C for 4h. S103. The carbon fibers treated in step S102 are heated in a hydrogen atmosphere at 500°C for 4 hours, and then cooled to room temperature to obtain modified carbon fibers.
[0023] Example 4 The preparation method of the solid electrolyte coating for lithium batteries based on sodium aminosulfonated cellulose includes the following steps: S1. Grind the solid electrolyte, which is LLZO, to a particle size of less than 50nm. S2. Add 10g of solid electrolyte treated in step S1 to 30g of deionized water, then add 1.25g of binder and 7.5g of conductive agent. The binder is sodium aminosulfonated cellulose and the conductive agent is modified carbon fiber. Stir and mix evenly to obtain a slurry. S3. The slurry obtained in step S2 is coated onto the surface of the substrate and dried to obtain a solid electrolyte coating. The preparation method of the above-mentioned modified carbon fiber includes the following steps: S101. Place 15g of carbon fiber into 150g of concentrated nitric acid with a concentration of 68wt%, heat to 95℃ for 3.6h, and then wash the carbon fiber treated with concentrated nitric acid with sufficient deionized water and dry it to constant weight at room temperature. S102. 10g of carbon fiber treated in step S101 is heated to 55°C in 150g of copper nitrate solution with a concentration of 1.5mol / L for 18 hours. After that, the carbon fiber is taken out and dried to constant weight at room temperature. The dried carbon fiber is then heated in air at 230°C for 2 hours. S103. The carbon fibers treated in step S102 are heated in a hydrogen atmosphere at 450°C for 3 hours, and then cooled to room temperature to obtain modified carbon fibers.
[0024] Four sets of solid electrolyte coatings were prepared through Examples 1-4 above. The solid electrolyte coatings were used to prepare the negative electrode sheets, resulting in four sets of negative electrode sheets. The specific preparation steps are as follows: Take a negative electrode current collector, specifically copper foil. After polishing the surface of the copper foil, immerse the copper foil in a mixed solution of potassium persulfate and sodium hydroxide for etching. The etching time can be 30-50 minutes, and the etching temperature can be 40-60℃. Specifically, the etching time is 40 minutes and the etching temperature is 50℃. After etching, the copper foil is washed with sufficient deionized water and then dried at room temperature. In a mixed solution of potassium persulfate and sodium hydroxide, the concentrations of potassium persulfate and sodium hydroxide can be 0.01-0.5 mol / L and 0.5-1 mol / L, respectively. Specifically, 0.02 mol / L of potassium persulfate and 0.6 mol / L of sodium hydroxide are used. The slurries prepared in Examples 1-4 were sprayed onto the different copper foil surfaces after treatment. After drying in an oven at 100°C for 2 hours, a solid electrolyte coating was obtained. Then, a negative electrode active material, composed of styrene-butadiene rubber (SBR), soft carbon, conductive graphite, and deionized water, was sprayed onto the solid electrolyte coating surface. The mass ratio of SBR, soft carbon, conductive graphite, and deionized water was 1:25:4:45. After spraying, the coating was dried in an oven at 150°C for 2 hours, forming a negative electrode active material coating on the solid electrolyte coating surface. The negative current collector, the solid electrolyte coating, and the negative electrode active material coating together constitute the negative electrode sheet.
[0025] The present invention also includes the following comparative examples. The slurries obtained in the following comparative examples are used to prepare solid electrolyte coatings on different copper foils, and the preparation of negative electrode active material coatings is completed (the preparation process of comparative examples 1-3 is exactly the same as that of the examples, while comparative example 4 is different, as shown below), and four sets of negative electrode sheets are obtained in the same way.
[0026] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that step S102 is omitted, while the remaining steps are exactly the same as in Example 1.
[0027] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that step S103 is omitted, while the remaining steps are exactly the same as in Example 1.
[0028] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the modified carbon fiber in step S2 is replaced with the same weight of unmodified carbon fiber, while the rest of the steps are exactly the same as in Example 1.
[0029] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the etching process of copper foil was omitted when preparing the negative electrode sheet, while the rest of the steps were exactly the same as in Example 1.
[0030] In this invention, the diameter of the carbon fiber is between 200-500 nm, and the length of the carbon fiber is between 5-15 μm.
[0031] The ionic conductivity and peel strength of the negative electrode sheets prepared in Examples 1-4 and Comparative Examples 1-4 were tested. The ionic conductivity was obtained using an electrochemical workstation (ZENNIUM, ZAHNER). The peel strength was measured according to the method in ASTM D903. The specific measurement results are shown in Table 1 below. As can be seen from the data in Table 1 above, in Comparative Example 1, the lack of copper ion adhesion resulted in a lack of copper particles on the carbon fiber surface, affecting the conductivity between the carbon fiber and the copper foil and reducing ionic conductivity. Furthermore, the copper particles enhanced the contact between the rough carbon fiber surface and the etched copper foil, improving their peel strength. In Comparative Example 2, the lack of a reduction operation significantly impacted the ionic conductivity of the entire negative electrode sheet, but had little effect on its peel strength. Comparative Example 3 used ordinary carbon fiber, whose relatively smooth surface resulted in poor contact with the relatively rough carbon fiber in the solid electrolyte, reducing conductivity. In addition, in Comparative Example 4, the lack of further etching of the copper foil weakened the contact ability between the rough carbon fiber and particles in the solid electrolyte coating and the copper foil, reducing its peel strength and also affecting ionic conductivity.
[0032] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a lithium battery solid electrolyte coating based on sodium aminosulfonated cellulose, characterized in that, The preparation method includes the following steps: S1. Grind the solid electrolyte to a particle size of less than 50nm; S2. Add the solid electrolyte treated in step S1 to deionized water, then add the binder and conductive agent, stir and mix evenly to obtain a slurry; S3. The slurry obtained in step S2 is coated onto the surface of the substrate and dried to obtain a solid electrolyte coating. The conductive agent is modified carbon fiber; The method for preparing the modified carbon fiber includes the following steps: S101. Place the carbon fiber in concentrated nitric acid and heat it for 2-4 hours. Then, wash the carbon fiber treated with concentrated nitric acid with sufficient deionized water and dry it to constant weight at room temperature. S102. The carbon fibers treated in step S101 are heated in copper nitrate solution for 10-20 hours. After that, the carbon fibers are taken out and dried to constant weight at room temperature. The dried carbon fibers are then heated in air at 220-270℃ for 1-4 hours. S103. The carbon fibers treated in step S102 are heated in a hydrogen atmosphere at 400-500℃ for 2-4 hours, and then cooled to room temperature to obtain modified carbon fibers. The solid electrolyte in step S1 is either LLZO or LATP; the binder in step S2 is sodium aminosulfonated cellulose.
2. The method for preparing a lithium battery solid electrolyte coating based on sodium aminosulfonated cellulose according to claim 1, characterized in that, In step S2, the mass ratio of solid electrolyte, conductive agent, deionized water, and adhesive is (5-10):(4-6):(20-25):
1.
3. The method for preparing a lithium battery solid electrolyte coating based on sodium aminosulfonated cellulose according to claim 1, characterized in that, In step S101, the concentration of concentrated nitric acid is 68 wt%, the carbon fiber is heated in concentrated nitric acid at a temperature of 80-100°C, and the mass ratio of concentrated nitric acid to carbon fiber added to concentrated nitric acid is 10:
1.
4. The method for preparing a lithium battery solid electrolyte coating based on sodium aminosulfonated cellulose according to claim 1, characterized in that, In step S102, the concentration of the copper nitrate solution is 0.5-2 mol / L, the mass ratio of the copper nitrate solution to the carbon fibers added to the copper nitrate solution is 15:1, and the temperature at which the carbon fibers are heated in the copper nitrate solution is 50-70℃.
5. A lithium battery solid electrolyte coating based on sodium aminosulfonated cellulose, characterized in that, It is prepared by the method for preparing a lithium battery solid electrolyte coating based on sodium aminosulfonated cellulose as described in any one of claims 1-4.
6. A negative electrode sheet, characterized in that, The negative electrode sheet includes the lithium battery solid electrolyte coating based on sodium aminosulfonated cellulose as described in claim 5; The negative electrode sheet also includes a negative current collector and a negative active material coating.
7. The negative electrode sheet according to claim 6, characterized in that, The negative electrode current collector is a copper foil, and the solid electrolyte coating is coated on both sides of the negative electrode current collector; the negative electrode active material coating is coated on the surface of the solid electrolyte coating; the negative electrode active material coating is composed of styrene-butadiene rubber (SBR), soft carbon, conductive graphite, and deionized water; the mass ratio of SBR, soft carbon, conductive graphite, and deionized water is 1:25:4:
45.
8. The negative electrode sheet according to claim 7, characterized in that, The copper foil needs to undergo surface treatment, and the method for surface treatment of the copper foil is as follows: After the copper foil surface is polished, it is immersed in a mixed solution of potassium persulfate and sodium hydroxide for etching. The etching time is 30-50 minutes and the etching temperature is 40-60℃. After etching, the copper foil is washed with sufficient deionized water and then dried at room temperature.
9. The negative electrode sheet according to claim 8, characterized in that, The concentrations of potassium persulfate and sodium hydroxide in the mixed solution are 0.01-0.5 mol / L and 0.5-1 mol / L, respectively.
Citation Information
Patent Citations
Heat-reduction metallization copper plating process for carbon fiber surface
CN104975278A
Compound foaming thermal-insulating cement board and preparation method thereof
CN108975825A
Modified carbon fiber reinforced silicone rubber thermal-insulation material and preparation method thereof
CN109233288A
Modified carbon fiber, preparation method thereof and modified carbon fiber reinforced cement-based material
CN113024141A
Fiber reinforced alloy material and preparation method thereof
CN115651341A